Low-protein diets supplemented with isoleucine alleviate lipid deposition in broilers through activating 5′ adenosine monophosphate-activated protein kinase and janus kinase 2/signal transducer and activator of transcription 3 signaling pathways - Shengnan Ma; Kai Zhang; Shuyan Shi; Xuemin Li; Chuanyan Che; Peng Chen; Huawei Liu (Poultry Science, 2023)
ABSTRACT: This study aimed to evaluate the effect of isoleucine (Ile) on growth performance, meat quality and lipid metabolism of broilers fed a low-protein diet (LPD). The 396 one-day-old male Cobb broilers were allocated to 4 treatment groups as follows: control diet (CON), LPD, LPD + 0.13% Ile (LPD-LI) and LPD + 0.26% Ile (LPD-HI), with nine replicates of 11 broilers each for 42 d. The Ile increased average daily gain, average daily feed intake, fiber density and the mRNA level of myosin heavy chain (MyHC)-I in breast muscle, and decreased feed to gain ratio, shear force, fiber diameter and the mRNA level of MyHC-IIb in breast muscle, which were impaired by the LPD. Compared to the LPD group, broilers in LPD-LI and LPD-HI groups had lower serum lipid levels, liver fat content, abdominal adipose percentage and mRNA levels of peroxisome proliferator-activated receptor-γ, CCAAT/enhancer binding protein-α, ki-67, topoisomerase II alpha (TOP2A) and thioredoxin-dependent peroxidase 2 in abdominal adipose and liver X receptors-α, sterol regulatory element binding protein 1 (SREBP1), acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS) in liver, and higher mRNA levels of peroxisome proliferator activated receptor-α, carnitine palmitoyl-transferase 1 (CPT-1), and acyl-CoA oxidase 1 (ACOX1) in liver, which were equal to the CON levels. A LPD supplemented with Ile decreased enzyme activities of ACC and FAS in liver and glycerol-3-phosphate dehydrogenase and TOP2A in abdominal adipose, and increased enzyme activities of CPT-1 and ACOX1 in liver. Furthermore, Ile supplementation enhanced the mRNA level of leptin receptor and protein levels of phospho-5′ adenosine monophosphate-activated protein kinase (AMPK), mechanistic target of rapamycin, ribosomal protein 70 S6 kinase, janus kinase 2 (JAK2), and signal transducer and activator of transcription 3 (STAT3), and decreased the protein level of SREBP1 in the liver of broilers in LPD group. In conclusion, dietary supplementation with Ile to 0.83% could improve growth performance and meat quality and alleviate lipid deposition of broilers fed a LPD through activating AMPK and JAK2/STAT3 signaling pathways.